Overvoltage protection of low voltage systems - Hasse, Peter (London, United Kingdom Institution of Engineering and Technology, 2000)
The following topics are dealt with; Damage due to lightning and surges; origin and effect of surges; protective measures, standards; components and protective devices: construction, effect and application.
Previous edition: London : P. Peregrinus on behalf of the Institute of Electrical Engineers, 1992.
Electronic reproduction.
Translated from the German.
Keywords: Overvoltage; Low voltage systems -- Protection; Electric power systems -- Protection; Electric apparatus and appliances -- Protection; Electronic books